Use of Force Account Procurement Method for Development of Small and Medium Contracting Firms in Mbeya - Stephen, Kaula (International Journal of Finance Research, 2021)
The study investigates on the value of using force account procurement method in development of small and medium contracting firms. To explicitly reveal what is behind the scene three objectives were formulated which were:-to examine the features of force account in procurement undertakings; to determine the value behind force account procurement method in procurement process towards development of SME and; to assess the bottleneck over effective enforcement of force account policy. The target population being (30) contractors, engineers and technicians employed with TANROADs, TARURA, TANESCO, and REA and those self employed (37) in Mbeya. Snow ball sampling technique was used to obtain a total of 67 respondents deduced. The semi-structured intereview and checklists schedules being used to gather the facts then descriptively and through the use of simple frequencies and percentage the reality was revealed:- force accounts involves local contractors by 100% executing contracts defined under force account policy to its end. Moreover force account is 100% local community participation procurement regularities; force account increases competence (70%); experience (66%) and financial capacitating (59%) of local contractors. Furthermore it was revealed that though projects assigned under force account are to be executed by indigenous contractors by 100% but from the field area it was found only 50% to be sustained. This gap of >50% of contracts under force account none executed was revealed to be caused by technical deficiency given the wilks’ lambda, λ<0.9; management incompetence given -X<5.0 and δ2>0.05; cases over (unethical practices reported >60%; financial difficulties >54.7%; and tax burden >60%).